Dietary Management of Labrador Retrievers with Subclinical Hepatic Copper Accumulation. (16th March 2015) - Fieten, H.; Biourge, V.C.; Watson, A.L.; Leegwater, P.A.J.; van den Ingh, T.S.G.A.M.; Rothuizen, J.
<x xml:space="preserve">Abstract</x> Background Genetic and environmental factors, including dietary copper intake, contribute to the pathogenesis of copper‐associated hepatitis in Labrador retrievers. Clinical disease is preceded by a subclinical phase in which copper accumulates in the liver. Objective To investigate the effect of a low‐copper, high‐zinc diet on hepatic copper concentration in Labrador retrievers with increased hepatic copper concentrations. Animals Twenty‐eight clinically healthy, client‐owned Labrador retrievers with a mean hepatic copper concentration of 919 ± 477 mg/kg dry weight liver (dwl) that were related to dogs previously diagnosed with clinical copper‐associated hepatitis. Methods Clinical trial in which dogs were fed a diet containing 1.3 ± 0.3 mg copper/Mcal and 64.3 ± 5.9 mg zinc/Mcal. Hepatic copper concentrations were determined in liver biopsy samples approximately every 6 months. Logistic regression was performed to investigate effects of sex, age, initial hepatic copper concentration and pedigree on the ability to normalize hepatic copper concentrations. Results In responders (15/28 dogs), hepatic copper concentrations decreased from a mean of 710 ± 216 mg/kg dwl copper to 343 ± 70 mg/kg dwl hepatic copper after a median of 7.1 months (range, 5.5–21.4 months). Dogs from a severely affected pedigree were at increased risk for inability to have their hepatic copper concentrations normalized with dietary treatment. Conclusions and Clinical Importance Feeding a low‐copper, high‐zinc diet resulted in a decrease in hepatic copper concentrations in a subset of clinically normal Labrador retrievers with previous hepatic copper accumulation. A positive response to diet may be influenced by genetic background. Determination of clinical benefit requires further study.